Carboxyl group copolyimide nanofiber film and preparation method thereof
By preparing carboxyl-group copolymer polyimide nanofiber films, the problems of high filtration resistance and low filtration efficiency of fine particulate matter in air filter materials have been solved, achieving a combination of high-efficiency filtration and good mechanical properties.
Patent Information
- Application Number
- CN202511191771.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-28
AI Technical Summary
Existing air filter materials have high filtration resistance, low filtration efficiency for fine particles, and poor mechanical properties.
A method for preparing carboxyl-group copolymerized polyimide nanofiber films was adopted. A polyamic acid solution was prepared by polycondensation reaction of specific mixed diamine monomers, electrospun into nanofiber films, and subjected to thermal imidization treatment to obtain carboxyl-group copolymerized polyimide nanofiber films.
It improves the filtration efficiency of fine particles, reduces filtration resistance, and maintains good mechanical properties at high temperatures.
Smart Images

Figure CN121023745A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thin film filtration material development technology, and relates to a carboxyl group copolyimide nanofiber thin film and its preparation method. Background Technology
[0002] Currently, ambient air pollution is one of the most challenging global security issues and has been identified as a global health priority in the sustainable development agenda. According to the latest report from the World Health Organization, 4.2 million people die each year due to long-term exposure to particulate matter. To address this problem, strategies such as pollution source control and air filtration have been proposed. Pollution source control refers to reducing particulate matter (PMs) emissions at the source, which typically requires complex equipment and considerable time. Air filtration, on the other hand, directly removes PMs from the air using filter media, offering advantages such as low maintenance costs, immediate air purification, and rapid improvement in air quality.
[0003] Polyimide (PI) exhibits high strength, corrosion resistance, and radiation resistance due to the presence of imide bonds in its main chain and the conjugation between the carbon-oxygen double bonds on the aromatic rings and the aromatic heterocycles. In particular, its highly conjugated structure and high aromaticity give PI fibers excellent thermal stability; its rigid chains, strong interactions, and high cohesive energy make it resistant to melting, maintaining good mechanical properties at temperatures as high as 500-600℃. Therefore, PI fibers are an ideal matrix material for high-temperature air filtration.
[0004] However, existing air filter materials suffer from technical problems such as high filtration resistance, low filtration efficiency for fine particles, and poor mechanical properties. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a carboxyl-group copolymerized polyimide nanofiber film and its preparation method, thereby solving the technical problems of high filtration resistance, low filtration efficiency of fine particulate matter, and poor mechanical properties in existing air filter materials.
[0006] This invention is achieved through the following technical solution: A method for preparing a carboxyl-group copolyimide nanofiber film includes the following steps: S1: A polyamic acid solution is obtained by polycondensation reaction of dianhydride monomer and mixed diamine monomer, followed by washing to precipitate and freeze-drying to obtain copolyamic acid powder; The mixed diamine monomer is 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl, or a mixture of p-phenylenediamine and 3,5-diaminobenzoic acid; S2: Dissolve the copolyamic acid powder in a polar aprotic solvent and stir until fully dissolved to obtain a copolyamic acid spinning solution; S3: Electrospinning is performed using the aforementioned copolyamic acid spinning solution to obtain a copolyamic acid nanofiber membrane; S4: The copolyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain the carboxyl group copolyimide nanofiber film.
[0007] Preferably, the molar ratio of 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl or p-phenylenediamine to 3,5-diaminobenzoic acid is (2~8):(8~2).
[0008] Preferably, in step S1, the temperature of the polycondensation reaction is 0~5℃ and the time is 4~6 h.
[0009] Preferably, in step S1, the freeze-drying time is 24~48 h.
[0010] Preferably, in step S2, the polar aprotic solvent is a mixture of one or more of N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide in any proportion.
[0011] Preferably, the mass concentration of polyamic acid in the copolymer polyamic acid spinning solution is 15% to 20%.
[0012] Preferably, during the electrospinning process, the spinning voltage is 16~20 kV, the spinning solution flow rate is 0.010~0.017 mL / min, and the distance between the needle and the receiving plate is 10~20 cm.
[0013] Preferably, the thermal imidization process specifically involves: at 5~10 o Heating to 100-150°C at a heating rate of C / min o Keep warm at C for 30-60 minutes, then for 5-10 minutes. o Heating to 200~250°C at a heating rate of C / min o C, keep warm for 30-60 minutes, and finally 5-10. o Heating to 300~350°C at a heating rate of C / min o C, keep warm for 30~60 minutes.
[0014] A carboxyl-group copolymerized polyimide nanofiber film is prepared by the method described above; the average diameter of the copolymerized polyimide nanofibers in the carboxyl-group copolymerized polyimide nanofiber film is 500~1200 nm; the mass factor of the copolymerized polyimide nanofibers is 0.0323~0.053 Pa. -1 .
[0015] The above-mentioned application of a carboxyl-group copolyimide nanofiber membrane in the field of air filtration.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing carboxyl-group copolymerized polyimide nanofiber films. First, in preparing the polyamic acid solution, a specific mixed diamine monomer is selected, including 3,5-diaminobenzoic acid containing carboxyl groups. This monomer participates in the polycondensation reaction with other diamine monomers, introducing carboxyl groups into the final product. The presence of carboxyl groups enhances the adsorption of fine particulate matter and improves filtration efficiency. Next, the copolymerized polyamic acid powder is dissolved in a polar aprotic solvent to prepare a spinning solution, and then the copolymerized polyamic acid nanofiber membrane is obtained using an electrospinning process. Electrospinning can prepare nanofiber membranes with high specific surface area and fine pore structure. This structure not only increases the contact area with air, facilitating the interception of more fine particulate matter, but also makes the air path more tortuous, effectively reducing filtration resistance. Finally, the copolymerized polyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain the carboxyl-group copolymerized polyimide nanofiber film. Polyimide itself possesses a highly conjugated structure and high aromaticity. Its rigid chains, strong interactions, and high cohesive energy make it resistant to melting and allow it to maintain good mechanical properties even at high temperatures, thus solving the problem of poor mechanical properties in existing materials. Furthermore, the average diameter of the co-polymerized polyimide nanofibers in this film is 500–1200 nm, and the mass factor is 0.0323–0.053 Pa. -1 This further demonstrates its advantages in filtration and mechanical properties, and is of great significance for expanding the application of electrospun nanofibers in the field of air filtration.
[0017] Furthermore, the molar ratio of 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl or p-phenylenediamine to 3,5-diaminobenzoic acid is (2~8):(8~2). If the proportion of 3,5-diaminobenzoic acid is too high, it will affect the regularity of the molecular structure of polyimide and reduce the mechanical properties and thermal stability of the film; if the proportion is too low, the carboxyl content will be insufficient, and the improvement in filtration efficiency for fine particulate matter will be limited.
[0018] Furthermore, in step S1, the temperature of the polycondensation reaction is 0~5℃ and the time is 4~6 h, which can reduce the heat during the reaction, increase the viscosity, and reduce the volatilization of organic solvents.
[0019] Furthermore, in step S1, the freeze-drying time is 24~48 h, which allows the solvent to fully sublimate and the copolyamic acid to maintain its original structure.
[0020] Furthermore, in step S2, the polar aprotic solvent is a mixture of one or more of N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide in any proportion. These polar aprotic solvents have strong polarity and excellent solubility for the copolyamic acid powder. They can quickly and completely dissolve the copolyamic acid powder to form a uniform spinning solution, avoiding the presence of particles or agglomerates in the spinning solution due to insufficient dissolution. This ensures the continuity and uniformity of the fibers during electrospinning and improves the quality of the nanofiber membrane.
[0021] Furthermore, the mass concentration of polyamic acid in the copolymer polyamic acid spinning solution is 15%~20%.
[0022] Furthermore, during the electrospinning process, the spinning voltage is 16~20 kV, the spinning solution flow rate is 0.010~0.017 mL / min, and the distance between the needle and the receiving plate is 10~20 cm, which can make the fiber output uniform and stable, and the yield high.
[0023] Furthermore, the thermal imidization process specifically involves: at 5~10 o Heating to 100-150°C at a heating rate of C / min o Keep warm at C for 30-60 minutes, then for 5-10 minutes. o Heating to 200~250°C at a heating rate of C / min o C, keep warm for 30-60 minutes, and finally 5-10. o Heating to 300~350°C at a heating rate of C / min o At temperature C, keep warm for 30-60 minutes to allow polyamic acid to be completely converted into polyimide. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a schematic flowchart of a method for preparing a carboxyl-group copolyimide nanofiber film according to the present invention; Figure 2These are optical photographs, scanning electron microscope images, and average fiber diameter diagrams of the polyimide nanofiber membranes and carboxyl-containing polyimide nanofiber films prepared by Comparative Examples 1-2 and Examples 1-5 of the present invention, wherein a and g correspond to Comparative Examples 1-2, and b, c, d, e, and f correspond to Examples 1-5, respectively. Figure 3 These are the infrared spectra of the polyimide nanofiber membranes and carboxyl-containing polyimide nanofiber films prepared by Comparative Examples 1-2 and Example 1 of the present invention. Figure 4 The filtration efficiency diagrams are of the polyimide nanofiber membranes and carboxyl-containing polyimide nanofiber films prepared by Comparative Examples 1-2 and Examples 1-5 of this invention. Figure 5 This is a pressure drop diagram of the polyimide nanofiber film containing carboxyl groups prepared in Example 4 of the present invention; Figure 6 This is a quality factor diagram of the polyimide nanofiber membranes and carboxyl-containing polyimide nanofiber films prepared by Comparative Examples 1-2 and Examples 1-5 of the present invention. Detailed Implementation
[0026] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0027] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0028] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0029] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0030] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0031] like Figure 1 As shown, this invention provides a method for preparing carboxyl-group copolyimide nanofiber films, comprising the following steps: S1: First, dianhydride monomer and mixed diamine monomer are subjected to low-temperature polycondensation to obtain polyamic acid (PAA) solution, and then polyamic acid powder is obtained after washing, precipitation and freeze-drying. The dianhydride monomer is one or a mixture of several of the following in any proportion: pyromellitic dianhydride (PMDA), hexafluorodianhydride, and 3,3',4,4'-benzophenone tetracarboxylic dianhydride. The mixed diamine monomers are 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminobiphenyl, or a mixture of p-phenylenediamine and 3,5-diaminobenzoic acid (DABA).
[0032] The molar ratio of 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl or p-phenylenediamine to 3,5-diaminobenzoic acid is (2~8):(8~2); The molar ratio of dianhydride monomer to mixed diamine monomer is (1~1.1):(0.95~1.05).
[0033] The polycondensation reaction is carried out at a temperature of 0-5℃ for 4-6 hours.
[0034] The freeze-drying time is 24~48 h.
[0035] S2: Add the obtained polyamic acid powder to a polar aprotic solvent and stir until fully dissolved to obtain a polyamic acid spinning solution. The mass concentration of polyamic acid in the polyamic acid spinning solution is 15 wt%~20 wt%.
[0036] The polar aprotic solvent is one or a mixture of several of N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide in any proportion. This polar aprotic solvent has strong polarity. S3: Polyamic acid nanofiber membranes are prepared using the polyamic acid spinning solution via electrospinning; the voltage during electrospinning is 16~20 kV, the flow rate of the spinning solution is 0.010~0.017 mL / min, and the distance between the needle and the receiving plate is 10~20 cm.
[0037] S4: The polyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain a carboxyl-group copolymerized polyimide nanofiber film; wherein, the thermal imidization process specifically involves heating the film at 5~10°C. o Heating to 100-150°C at a heating rate of C / min o Keep warm at C for 30-60 minutes, then for 5-10 minutes. o Heating to 200~250°C at a heating rate of C / min o C, keep warm for 30-60 minutes, and finally 5-10. o Heating to 300~350°C at a heating rate of C / min o C, keep warm for 30~60 minutes.
[0038] This invention discloses a carboxyl-group copolymerized polyimide nanofiber film prepared by the above-described method. In the carboxyl-group-containing polyimide nanofiber film, the average diameter of the carboxyl-group-containing polyimide nanofibers is 500–1300 nm; the average pore size of the carboxyl-group-containing polyimide nanofibers is 10–20 nm; and the quality factor of the carboxyl-group-containing polyimide nanofibers is 0.032–0.053 Pa. -1 .
[0039] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0040] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0041] Comparative Example 1 Preparation of polyamic acid (PAA) precursor solid: PMDA and ODA were added to 120 mL of DMF solution at a molar ratio of 1.03:1. The specific steps are as follows: First, 100 mL of DMF and 10 g of 4,4'-diaminodiphenyl ether (ODA) were weighed and added to a three-necked flask. The mixture was then heated at low temperature. oDissolve the PAA solution by stirring at C. Then, weigh 11.22 g of pyromellitic anhydride (PMDA) and add it in four portions, 10 min apart. Rinse the beaker and flask walls with the remaining 20 mL of DMF. Stir for 6 h, and stop the reaction when the climbing effect occurs, to obtain a PAA solution. When the PAA solution is stretched and oriented along the stirring shaft and wrapped around the shaft during stirring, i.e., when the climbing effect occurs, slowly pour the PAA into 2 L of deionized water to precipitate it. After washing several times, pre-freeze it in a refrigerator, then freeze-dry it for 24 h to obtain solid PAA, grind it, and store it at low temperature for later use.
[0042] Preparation of PAA nanofiber membrane: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity of 30%, distance between needle tip and receiving plate of 16 cm) to prepare PAA fibers. The specific process is as follows: 3 g of the PAA powder prepared above was weighed and dissolved in 7 mL of DMF solution. After stirring at low temperature for 4 h, a light yellow PAA spinning solution with a mass concentration of 30% was obtained. The electrospinning voltage was set to 17 kV and the flow rate was 0.015 mL / min, and electrospinning was carried out to obtain PAA nanofiber film.
[0043] Preparation of polyimide nanofiber membranes: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 10 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o C, heat for 30 min to obtain polyimide nanofiber membrane (labeled as 10:0 PI).
[0044] Comparative Example 2 Preparation of solid polyamic acid (CPAA) containing carboxyl groups: In 120 mL of DMF solution, PMDA and DABA were added at a molar ratio of 1.03:1. The specific steps are as follows: First, 100 mL of DMF and 10 g of 3,5-diaminobenzoic acid (DABA) were weighed and added to a three-necked flask. The mixture was then heated at low temperature. oDissolve the CPAA solution by stirring at C. Then, weigh 14.7659 g of pyromellitic anhydride (PMDA) and add it in four portions, 10 min apart. Rinse the beaker and flask walls with the remaining 20 mL of DMF. Stir for 6 h, and stop the reaction when the climbing effect occurs, to obtain a CPAA solution. When the CPAA solution is stretched and oriented along the stirring shaft and wrapped around the shaft during stirring, i.e., when the climbing effect occurs, slowly pour the CPAA into 2 L of deionized water to precipitate it. After washing several times, pre-freeze it in a refrigerator, then freeze-dry it for 24 h to obtain solid CPAA, grind it, and store it at low temperature for later use.
[0045] Preparation of polyamic acid (CPAA) nanofiber membranes containing carboxyl groups: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity 30%, needle tip distance from receiving plate 16 cm) to prepare CPAA fibers. The specific process is as follows: 3 g of the CPAA powder prepared above was weighed and dissolved in 7 ml of DMF solution. After stirring at low temperature for 4 h, a black CPAA spinning solution with a mass concentration of 30% was obtained. The electrospinning voltage was set to 17 kV and the flow rate was 0.015 mL / min, and electrospinning was carried out to obtain CPAA nanofiber films.
[0046] Preparation of polyimide nanofiber membranes containing carboxyl groups: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 10 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o At temperature C, heat for 30 min to obtain a polyimide nanofiber membrane containing carboxyl groups (labeled as 0:10 CPI).
[0047] Example 1 Preparation of solid polyamic acid (CPAA) containing carboxyl groups: In 120 mL of DMF solution, PMDA, ODA, and DABA were added at a molar ratio of dianhydride to mixed diamine of 1.03:1, wherein the molar ratio of ODA to DABA was 2:8. The specific steps are as follows: First, 100 mL of DMF, 2.4756 g of 4,4'-diaminodiphenyl ether (ODA), and 7.5244 g of 3,5-diaminobenzoic acid (DABA) were weighed and added to a three-necked flask, and the mixture was heated at low temperature for 1 minute. oDissolve the CPAA solution by stirring at C. Then, weigh out 13.9292 g of pyromellitic anhydride (PMDA) and add it in four portions, 10 min apart. Rinse the beaker and flask walls with the remaining 20 mL of DMF. Stir for 6 h, and stop the reaction when the rod-climbing effect occurs, yielding a CPAA solution. Then, slowly pour the CPAA into 2 L of deionized water to precipitate it, wash it several times, pre-freeze it in a refrigerator, and then freeze-dry it for 24 h to obtain solid CPAA. Grind the solid and store it at low temperature for later use.
[0048] Preparation of polyamic acid (CPAA) nanofiber membranes containing carboxyl groups: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity 30%, needle tip distance from receiving plate 16 cm) to prepare CPAA fibers. The specific process is as follows: 3 g of the CPAA powder prepared above was weighed and dissolved in 7 mL of DMF solution. After stirring at low temperature for 4 h, a black CPAA spinning solution with a mass concentration of 30% was obtained. The electrospinning voltage was set to 17 kV and the flow rate was 0.015 mL / min, and electrospinning was carried out to obtain CPAA nanofiber films.
[0049] Preparation of polyimide (CPI) nanofiber membranes containing carboxyl groups: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 5 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o At temperature C, heat for 30 min to obtain polyimide nanofiber membrane (labeled as 2:8 CPI).
[0050] Example 2 Preparation of carboxyl-containing polyamic acid (CPAA) solid: In 120 mL of DMF solution, PMDA, ODA, and DABA were added according to a molar ratio of dianhydride to mixed diamine of 1.03:1, wherein the molar ratio of ODA to DABA was 4:6. The specific steps are as follows: First, 100 mL of DMF, 4.6734 g of 4,4'-diaminodiphenyl ether (ODA), and 5.3268 g of 3,5-diaminobenzoic acid (DABA) were weighed and added to a three-necked flask, and then heated at low temperature. oDissolve the CPAA solution by stirring at C. Then, weigh out 13.1114 g of pyromellitic anhydride (PMDA) and add it in four portions, 10 min apart. Rinse the beaker and flask walls with the remaining 20 mL of DMF. Stir for 6 h, and stop the reaction when the rod-climbing effect occurs, yielding a CPAA solution. Then, slowly pour the CPAA into 2 L of deionized water to precipitate it, wash it several times, pre-freeze it in a refrigerator, and then freeze-dry it for 24 h to obtain solid CPAA. Grind the solid and store it at low temperature for later use.
[0051] Preparation of polyamic acid (CPAA) nanofiber membranes containing carboxyl groups: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity 30%, needle tip distance from receiving plate 16 cm) to prepare PAA fibers. The specific process is as follows: 2.9 g of the CPAA powder prepared above was weighed and dissolved in 10 mL of DMF solution. After stirring at low temperature for 4 h, a black CPAA spinning solution with a mass concentration of 29% was obtained. The electrospinning voltage was set to 24 kV and the flow rate was 0.017 mL / min, and electrospinning was carried out to obtain CPAA nanofiber films.
[0052] Preparation of polyimide (CPI) nanofiber membranes containing carboxyl groups: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 5 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o C, heat for 30 min to obtain a polyimide nanofiber membrane containing carboxyl groups (labeled as 4:6 CPI).
[0053] Example 3 Preparation of solid polyamic acid (CPAA) containing carboxyl groups: In 120 mL of DMF solution, PMDA, ODA, and DABA were added according to a molar ratio of dianhydride to mixed diamine of 1.03:1, wherein the molar ratio of ODA to DABA was 5:5. The specific steps are as follows: First, 100 mL of DMF, 5.6826 g of 4,4'-diaminodiphenyl ether (ODA), and 4.3178 g of 3,5-diaminobenzoic acid (DABA) were weighed and added to a three-necked flask and stirred to dissolve at a low temperature of 4 °C. Then, 6.3804 g of pyromellitic anhydride (PMDA) was weighed and added in four portions, with an interval of 10 min between each addition. The beaker and flask walls were rinsed with the remaining 20 mL of DMF. The mixture was stirred for 6 h, and the reaction ended after the rod-climbing effect was observed, thus obtaining the CPAA solution. Then, CPAA was slowly poured into 2 L of deionized water to precipitate it and was washed several times. It was then placed in a refrigerator for pre-freezing and freeze-dried for 24 h to obtain solid CPAA. After grinding, it was stored at low temperature for later use.
[0054] Preparation of CPAA nanofiber membrane: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity 30%, needle tip distance from receiving plate 16 cm) to prepare CPAA fibers. The specific process is as follows: 3 g of the above-prepared CPAA powder was weighed and dissolved in 10 mL of DMF solution. After stirring at low temperature for 4 h, a black CPAA spinning solution with a mass concentration of 30% was obtained. The electrospinning voltage was set to 24 kV and the flow rate was 0.017 mL / min, and electrospinning was carried out to obtain CPAA nanofiber film.
[0055] Preparation of polyimide (CPI) fiber membranes containing carboxyl groups: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 5 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o C, heat for 30 min to obtain polyimide nanofiber membrane (labeled as 5:5 CPI).
[0056] Example 4 Preparation of solid polyamic acid (CPAA) containing carboxyl groups: In 120 mL of DMF solution, PMDA, ODA, and DABA were added at a molar ratio of dianhydride to mixed diamine of 1.03:1, wherein the molar ratio of ODA to DABA was 6:4. The specific steps are as follows: First, 100 mL of DMF, 6.648 g of 4,4'-diaminodiphenyl ether (ODA), and 3.363 g of 3,5-diaminobenzoic acid (DABA) were weighed and added to a three-necked flask, and then heated at low temperature (4°C). o Dissolve the CPAA solution by stirring at C. Then, weigh out 12.424 g of pyromellitic anhydride (PMDA) and add it in four portions, 10 min apart. Rinse the beaker and flask walls with the remaining 20 mL of DMF. Stir for 6 h, and stop the reaction when the rod-climbing effect occurs, yielding a CPAA solution. Then, slowly pour the CPAA into 2 L of deionized water to precipitate it. After washing several times, pre-freeze the solution in a refrigerator, then freeze-dry it for 24 h to obtain solid CPAA. Grind the solid and store it at low temperature for later use.
[0057] Preparation of CPAA nanofiber membrane: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity 30%, needle tip distance from receiving plate 16 cm) to prepare CPAA fibers. The specific process is as follows: 3 g of the above-prepared CPAA powder was weighed and dissolved in 10 mL of DMF solution. After stirring at low temperature for 4 h, a black CPAA spinning solution with a mass concentration of 30% was obtained. The electrospinning voltage was set to 24 kV and the flow rate was 0.017 mL / min, and electrospinning was carried out to obtain CPAA nanofiber film.
[0058] Preparation of polyimide fiber membranes containing carboxyl groups: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 5 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o At temperature C, heat for 30 min to obtain polyimide nanofiber membrane (labeled as 6:4 CPI).
[0059] Example 5 Preparation of solid polyamic acid (CPAA) containing carboxyl groups: In 120 mL of DMF solution, PMDA, ODA, and DABA were added at a molar ratio of dianhydride to mixed diamine of 1.03:1, wherein the molar ratio of ODA to DABA was 8:2. The specific steps are as follows: First, 100 mL of DMF, 8.4097 g of 4,4'-diaminodiphenyl ether (ODA), and 1.5976 g of 3,5-diaminobenzoic acid (DABA) were weighed and added to a three-necked flask, and then heated at low temperature (4°C). o Dissolve the CPAA solution by stirring at C. Then, weigh out 11.7948 g of pyromellitic anhydride (PMDA) and add it in four portions, 10 min apart. Rinse the beaker and flask walls with the remaining 20 mL of DMF. Stir for 6 h, and stop the reaction when the rod-climbing effect occurs, yielding a CPAA solution. Then, slowly pour the CPAA into 2 L of deionized water to precipitate it, wash it several times, pre-freeze it in a refrigerator, and then freeze-dry it for 24 h to obtain solid CPAA. Grind the solid and store it at low temperature for later use.
[0060] Preparation of CPAA nanofiber membrane: The concentration of the spinning solution was adjusted, and the spinning process was carried out using an electrospinning device (ambient humidity 30%, needle tip distance from receiving plate 16 cm) to prepare CPAA fibers. The specific process is as follows: 3 g of the above-prepared CPAA powder was weighed and dissolved in 10 mL of DMF solution. After stirring at low temperature for 4 h, a black CPAA spinning solution with a mass concentration of 30% was obtained. The electrospinning voltage was set to 24 kV and the flow rate was 0.017 mL / min, and electrospinning was carried out to obtain CPAA nanofiber film.
[0061] Preparation of polyimide (CPI) fiber membranes containing carboxyl groups: The above-mentioned films were subjected to a staged heating reaction in a high-temperature tube furnace under Ar atmosphere, followed by post-treatment: at 5... o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 5 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o At temperature C, heat for 30 min to obtain polyimide nanofiber membrane (labeled as 8:2 CPI).
[0062] Furthermore, the technical solution of the present invention will be explained with reference to the accompanying drawings.
[0063] Figure 2 Optical and scanning electron microscope images of polyimide nanofiber membranes and carboxyl-containing polyimide nanofiber membranes, from... Figure 2It can be seen that the diameter of polyimide nanofibers without the addition of 3,5-diaminobenzoic acid (DABA) is relatively small, at 358.92 nm. After the addition of DABA, the diameter of polyimide nanofibers containing carboxyl groups increases significantly, with an average of 836 nm.
[0064] Figure 3 Infrared spectra of polyamic acid nanofiber membranes, polyimide nanofiber membranes, polyamic acid nanofibers containing carboxyl groups, and polyimide nanofiber membranes containing carboxylic acid groups. Figure 3 It can be seen that polyamic acid nanofiber membranes are available in the 3030-3700 cm⁻¹ range. -1 The presence of a broad absorption peak at this location indicates the presence of -NH and -COOH groups; the characteristic peak of the imide ring is at 1780 cm⁻¹. -1 1719 cm -1 1377 cm -1 720 cm -1 The corresponding vibrations are -C=O asymmetric stretching vibration, -C=O symmetric stretching vibration, CNC stretching vibration, and OC-N-CO deformation vibration, respectively. In addition, due to the dehydration and cyclization of PAA and CPAA, the broad absorption peaks of -NH and -COOH disappear, and the absorption peak of -C=O exhibits a blue shift. This is because -COOH is an electron-withdrawing group, which can draw electrons away from the aromatic rings and imide chains of PI and CPI through inductive effects, leading to a decrease in the electron cloud density of the CN bond, an increase in vibrational frequency, and a shift of the wavenumber towards higher wavenumbers, thus resulting in the blue shift. Therefore, after the programmed temperature treatment, PAA and CPAA have completely dehydrated and cyclized into PI and CPI.
[0065] Figures 4-6 The diagram shows the air filtration performance of polyimide nanofiber membranes and polyimide nanofiber membranes containing carboxyl groups at room temperature. Figure 4 The effects of different spinning times, different diamine ratios (PI) and CPI nanofiber membranes on PM2.5 at room temperature were demonstrated. 0.3 The filtration efficiency was measured. It can be seen that the filtration efficiency initially increases and then decreases with increasing spinning time and DABA content. The highest filtration efficiency (99.63%) was achieved when the spinning time was 40 min and the diamine ratio was 6:4. This is likely because increasing the DABA content increases the fiber diameter, leading to a relatively smaller specific surface area, increased pore size, and weakened interception of particulate matter, thus reducing filtration efficiency. The filtration performance of the filter material also depends on the pressure drop before and after the filtration process; therefore, a quality factor (Q) is generally selected. F To comprehensively evaluate the filtration performance of filter materials. Figure 5 , 6 It can be seen that when spinning for 40 minutes, the pressure drop of CPI (6:4) is only 93 Pa, and the quality factor is 0.053 Pa.-1 .
[0066] Example 6 A method for preparing a carboxyl-containing copolyimide nanofiber film includes the following steps: S1: First, completely dissolve both diamine monomers in a highly polar solvent, then add the dianhydride monomer in batches at 1... o The reaction was carried out at C for 4 h to obtain a viscous polyamic acid solution. The polyamic acid solution was then slowly poured into deionized water to solidify. The solution was washed multiple times until no white solvent material precipitated out of the polyamic acid solid in the water. Finally, the solidified polyamic acid solid was freeze-dried for 24-48 h and ground to obtain a yellow polyamic acid powder.
[0067] The diamine monomers are 4,4'-diaminodiphenyl ether (ODA) and 3,5-diaminobenzoic acid (DABA), the dianhydride monomer is pyromellitic anhydride (PMDA), the molar ratio of the diamine monomer to the dianhydride monomer is 1:1.03, and the strongly polar solvent is N,N'-dimethylformamide (DMF).
[0068] S2: Under low temperature conditions, the obtained polyamic acid powder is dissolved in N,N'-dimethylformamide (DMF) and stirred until the polyamic acid powder is completely dissolved to obtain a polyamic acid spinning solution. The mass concentration of polyamic acid in the polyamic acid spinning solution is 30 wt%.
[0069] S3: Polyamic acid nanofiber membranes are prepared using the polyamic acid spinning solution via electrospinning; the electrospinning voltage is 17 kV, the spinning solution flow rate is 0.015 mL / min, and the distance between the needle and the receiving plate is 15 cm.
[0070] S4: The polyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain a polyimide nanofiber membrane; wherein, the thermal imidization process specifically involves, at 5 o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 5 o Heating to 250°C at a heating rate of C / min o C, keep warm for 30 minutes, and finally at 5 o Heating to 320°C at a heating rate of C / min o C, keep warm for 30 minutes.
[0071] The polyimide nanofiber layer containing carboxyl groups prepared in this embodiment has an average diameter of 673.3 nm, an average pore size of 14 nm, and a quality factor of 0.053 Pa. -1 .
[0072] Example 7 A method for preparing a carboxyl-group copolyimide nanofiber film includes the following steps: S1: First, dianhydride monomer and mixed diamine monomer are subjected to low-temperature polycondensation to obtain polyamic acid (PAA) solution, and then polyamic acid powder is obtained after washing, precipitation and freeze-drying. The dianhydride monomer is hexafluorodianhydride; The mixed diamine monomer is a mixture of 4,4'-diaminobiphenyl and 3,5-diaminobenzoic acid (DABA).
[0073] The molar ratio of 4,4'-diaminobiphenyl to 3,5-diaminobenzoic acid is 1:4; The molar ratio of dianhydride monomer to mixed diamine monomer is 1:0.95.
[0074] The polycondensation reaction was carried out at a temperature of 0°C for 6 hours.
[0075] The freeze-drying time is 24 hours.
[0076] S2: Add the obtained polyamic acid powder to a polar aprotic solvent and stir until fully dissolved to obtain a polyamic acid spinning solution with a polyamic acid mass concentration of 15 wt%.
[0077] The polar aprotic solvent is N,N'-dimethylacetamide; S3: Polyamic acid nanofiber membranes are prepared using the polyamic acid spinning solution via electrospinning; the voltage during electrospinning is 16 kV, the flow rate of the spinning solution is 0.010 mL / min, and the distance between the needle and the receiving plate is 10 cm.
[0078] S4: The polyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain a carboxyl-group copolymerized polyimide nanofiber film; wherein, the thermal imidization process specifically involves, at 5 o Heating to 100°C at a heating rate of C / min o Keep warm at C for 60 minutes, then at 5 o Heating to 200°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 5 o Heating to 300°C at a heating rate of C / min o C, keep warm for 60 minutes.
[0079] In the carboxyl-group copolyimide nanofiber film prepared in this embodiment, the average diameter of the copolyimide nanofibers is 500 nm; the mass factor of the copolyimide nanofibers is 0.0323 Pa. -1 .
[0080] Example 8 A method for preparing a carboxyl-group copolyimide nanofiber film includes the following steps: S1: First, dianhydride monomer and mixed diamine monomer are subjected to low-temperature polycondensation to obtain polyamic acid (PAA) solution, and then polyamic acid powder is obtained after washing, precipitation and freeze-drying. The dianhydride monomer is hexafluorodianhydride; the mixed diamine monomer is a mixture of p-phenylenediamine and 3,5-diaminobenzoic acid, wherein the molar ratio of p-phenylenediamine to 3,5-diaminobenzoic acid is 5:5; and the molar ratio of the dianhydride monomer to the mixed diamine monomer is 1.1:1.05. The polycondensation reaction is carried out at 5°C for 4 hours. The freeze-drying time is 48 hours.
[0081] S2: Add the obtained polyamic acid powder to a polar aprotic solvent and stir until fully dissolved to obtain a polyamic acid spinning solution with a polyamic acid mass concentration of 20 wt%.
[0082] Among them, the polar aprotic solvent is N-methylpyrrolidone; S3: Polyamic acid nanofiber membranes are prepared using the polyamic acid spinning solution via electrospinning; the voltage during electrospinning is 20 kV, the flow rate of the spinning solution is 0.017 mL / min, and the distance between the needle and the receiving plate is 20 cm.
[0083] S4: The polyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain a carboxyl-group copolymerized polyimide nanofiber film; wherein, the thermal imidization process specifically involves, at 10 o Heating to 150°C at a heating rate of C / min o Keep warm at C for 30 minutes, then at 10 o Heating to 250°C at a heating rate of C / min o C, keep warm for 60 minutes, and finally at 10 o Heating to 350°C at a heating rate of C / min o C, keep warm for 60 minutes.
[0084] In the carboxyl-group copolyimide nanofiber film prepared in this embodiment, the average diameter of the copolyimide nanofibers is 1200 nm; the mass factor of the copolyimide nanofibers is 0.053 Pa. -1 .
[0085] Example 9 A method for preparing a carboxyl-group copolyimide nanofiber film includes the following steps: S1: First, dianhydride monomer and mixed diamine monomer are subjected to low-temperature polycondensation to obtain polyamic acid (PAA) solution, and then polyamic acid powder is obtained after washing, precipitation and freeze-drying. The dianhydride monomer is 3,3',4,4'-benzophenone tetracarboxylic dianhydride; The mixed diamine monomers were a mixture of p-phenylenediamine and 3,5-diaminobenzoic acid, with a molar ratio of p-phenylenediamine to 3,5-diaminobenzoic acid of 8:2; the molar ratio of dianhydride monomers to mixed diamine monomers was 1:1. The polycondensation reaction was carried out at 3°C for 5 hours. The freeze-drying time was 35 hours.
[0086] S2: Add the obtained polyamic acid powder to a polar aprotic solvent and stir until fully dissolved to obtain a polyamic acid spinning solution with a polyamic acid mass concentration of 17 wt%.
[0087] The polar aprotic solvent is dimethyl sulfoxide; S3: Polyamic acid nanofiber membranes are prepared using the polyamic acid spinning solution via electrospinning; the voltage during electrospinning is 18 kV, the flow rate of the spinning solution is 0.015 mL / min, and the distance between the needle and the receiving plate is 15 cm.
[0088] S4: The polyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain a carboxyl-group copolymerized polyimide nanofiber film; wherein, the thermal imidization process specifically involves, at 7 o Heating to 120°C at a heating rate of C / min o Keep warm at C for 40 minutes, then at 7 o Heating to 230°C at a heating rate of C / min o C, keep warm for 40 minutes, and finally at 7 o Heating to 330°C at a heating rate of C / min o C, keep warm for 50 minutes.
[0089] In the carboxyl-group copolyimide nanofiber film prepared in this embodiment, the average diameter of the copolyimide nanofibers is 800 nm; the mass factor of the copolyimide nanofibers is 0.044 Pa. -1 .
[0090] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a carboxyl-group copolyimide nanofiber film, characterized in that, Includes the following steps: S1: A polyamic acid solution is obtained by polycondensation reaction of dianhydride monomer and mixed diamine monomer, followed by washing to precipitate and freeze-drying to obtain copolyamic acid powder; The mixed diamine monomer is 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl, or a mixture of p-phenylenediamine and 3,5-diaminobenzoic acid; S2: Dissolve the copolyamic acid powder in a polar aprotic solvent and stir until fully dissolved to obtain a copolyamic acid spinning solution; S3: Electrospinning is performed using the aforementioned copolyamic acid spinning solution to obtain a copolyamic acid nanofiber membrane; S4: The copolyamic acid nanofiber membrane is subjected to thermal imidization treatment to obtain the carboxyl group copolyimide nanofiber film.
2. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, The molar ratio of 4,4'-diaminodiphenyl ether, 4,4'-diaminobiphenyl or p-phenylenediamine to 3,5-diaminobenzoic acid is (2~8):(8~2).
3. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, In step S1, the polycondensation reaction is carried out at a temperature of 0-5°C for 4-6 hours.
4. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, In step S1, the freeze-drying time is 24~48 h.
5. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, In step S2, the polar aprotic solvent is a mixture of one or more of N,N'-dimethylformamide, N,N'-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide in any proportion.
6. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, The mass concentration of polyamic acid in the copolymer polyamic acid spinning solution is 15%~20%.
7. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, During the electrospinning process, the spinning voltage is 16~20 kV, the spinning solution flow rate is 0.010~0.017 mL / min, and the distance between the needle and the receiving plate is 10~20 cm.
8. The method for preparing a carboxyl-group copolyimide nanofiber film according to claim 1, characterized in that, The thermal imidization process specifically involves: at 5~10 o Heating to 100-150°C at a heating rate of C / min o Keep warm at C for 30-60 minutes, then for 5-10 minutes. o Heating to 200~250°C at a heating rate of C / min o C, keep warm for 30-60 minutes, and finally 5-10. o Heating to 300~350°C at a heating rate of C / min o C, keep warm for 30~60 minutes.
9. A carboxyl-group copolyimide nanofiber film, characterized in that, The nanofiber film is prepared by the method according to any one of claims 1 to 8; the average diameter of the copolyimide nanofibers in the carboxyl group copolymerized polyimide nanofiber film is 500-1200 nm; the mass factor of the copolyimide nanofibers is 0.0323-0.053 Pa. -1 .
10. The application of the carboxyl-group copolyimide nanofiber film as described in claim 9 in the field of air filtration.